2008
DOI: 10.1007/s11606-008-0707-9
|View full text |Cite
|
Sign up to set email alerts
|

How Do Community Practitioners Decide Whether to Prescribe Antibiotics for Acute Respiratory Tract Infections?

Abstract: Based on hypothetical cases of ARI, community practitioners prescribed antibiotics at twice the rate of faculty following CDC practice guidelines. Practitioners were most strongly influenced by duration of illness. The effect of duration was strongest when accompanied by fever or productive cough, suggesting that these situations would be important areas for practitioner education and further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…To allow comparison between emergency physicians and community practitioners, we used the same methodology of judgment analysis to study Wisconsin ED physicians as that previously reported for Colorado community practitioners [14]. Judgment analysis models judgment using regression techniques to infer weights of clinical factors in hypothetical clinical vignettes based on subjects' estimates of their likelihood of prescribing antibiotics for each vignette.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To allow comparison between emergency physicians and community practitioners, we used the same methodology of judgment analysis to study Wisconsin ED physicians as that previously reported for Colorado community practitioners [14]. Judgment analysis models judgment using regression techniques to infer weights of clinical factors in hypothetical clinical vignettes based on subjects' estimates of their likelihood of prescribing antibiotics for each vignette.…”
Section: Methodsmentioning
confidence: 99%
“…We used the same 20 vignettes used in the earlier study of community practitioners' prescribing of antibiotics in ARI [14]. After reading each case, respondents were asked whether or not they would prescribe antibiotics for this patient [yes/no] and how likely it was they would prescribe antibiotics (0 -100 scale).…”
Section: Paper Case Vignettesmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicians commonly ask their patients about the colour of their sputum and how unwell they are feeling to inform their decision of whether or not to prescribe an antibiotic for acute cough, based on the assumption that purulence is more likely to reflect a bacterial cause and predict improved outcomes from antibiotics [6][7][8]. Clinicians regard patients who feel both systemically unwell and who also produce discoloured sputum an even higher priority for an antibiotic prescription [9][10][11]. Guidelines identify purulent sputum as one of a cluster of clinical features that should alert clinicians to possible serious lung infection [12].…”
mentioning
confidence: 99%